2013
DOI: 10.1093/humupd/dmt030
|View full text |Cite|
|
Sign up to set email alerts
|

What is the optimal means of preparing the endometrium in frozen–thawed embryo transfer cycles? A systematic review and meta-analysis

Abstract: BACKGROUND Frozen-thawed embryo transfer (FET) enables surplus embryos derived from IVF or IVF-ICSI treatment to be stored and transferred at a later date. In recent years the number of FET cycles performed has increased due to transferring fewer embryos per transfer and improved laboratory techniques. Currently, there is little consensus on the most effective method of endometrium preparation prior to FET. METHODS Using both MEDLINE and EMBASE database a systematic review and meta-analysis of literature was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(96 citation statements)
references
References 65 publications
7
74
1
8
Order By: Relevance
“…A systematic review and meta-analysis published in 2013 compared clinical and ongoing pregnancy rates, as well as live birth rates, in (a) true natural cycle FET (NC-FET), (b) modified NC-FET with hCG, (c) artificial cycle FET (AC-FET), and (d) AC-FET supplemented with GnRH agonists. The study revealed no significant advantage of any specific approach to prepare the endometrium for FET in terms of clinical pregnancy rates or live birth rates [75]. The results were in line with the previous systematic review published in 2008 [76].…”
Section: Freeze-all For Whom?supporting
confidence: 89%
“…A systematic review and meta-analysis published in 2013 compared clinical and ongoing pregnancy rates, as well as live birth rates, in (a) true natural cycle FET (NC-FET), (b) modified NC-FET with hCG, (c) artificial cycle FET (AC-FET), and (d) AC-FET supplemented with GnRH agonists. The study revealed no significant advantage of any specific approach to prepare the endometrium for FET in terms of clinical pregnancy rates or live birth rates [75]. The results were in line with the previous systematic review published in 2008 [76].…”
Section: Freeze-all For Whom?supporting
confidence: 89%
“…In a recent review and meta-analysis, no single endometrial preparation method for FET was found to be superior, with all methods being equally effective in terms of ongoing pregnancy [16]. The connecting protocol, therefore, needs to maintain the existing cost-effectivity and predictability of treatment without compromising reproductive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the 14th day of estrogen therapy a transvaginal ultrasound scan (TVUS) was performed to measure endometrial thickness. An endometrial thickness of >7 mm was considered most optimal [16,22]. On the day of scan, serum progesterone was also measured, with FET cycles cancelled if the serum progesterone concentration was above an arbitrary chosen threshold (2 ng/mL).…”
Section: Endometrial Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, FET after cryopreservation of all embryos has been widely used either to perform preimplantation genetic screening (PGS) or to minimize the risk of developing ovarian hyperstimulation syndrome (OHSS) [2]. FET can be accomplished with various endometrial preparation protocols including programmed cycles involving the use of exogenous estrogen and progesterone, or using the patient's natural cycle and associated endogenous hormones [3]. NC-FET is considered by many clinicians the preferred method for women with regular ovulatory menstrual cycles because it does not require long-term exogenous hormonal replacement [4].…”
Section: Introductionmentioning
confidence: 99%